Let’s take some examples

####
**
Add
**
**
1/3
**
**
&
**
**
4/3
**

1/3 + 4/3

*
Since denominator is same,
*

*
*
*
we add numerators
*

= (1+ 4)/3

**
= 5/3
**

####
**
Subtract
**
**
6/9
**
**
from
**
**
2/9
**

2/9 − 6/9

*
Since denominator is same,
*

*
we add
*
*
numerators
*

= (2 - 6)/9

**
= (-4)/9
**

####
**
Subtract
**
**
1/2
**
**
&
**
**
1/5
**

1/2 − 1/5

= (1 × 5 - 1 × 2)/(2 × 5)

= (5 - 2)/6

=
**
3/10
**

####
**
Add
**
**
1/2
**
**
&
**
**
1/3
**

1/2 + 1/3

= (1 × 3 + 1 × 2)/(2 × 3)

= (3 + 2)/6

**
= 5/6
**

####
**
Add
**
**
1/2
**
**
&
**
**
(-1)/3
**

1/2 + ((-1)/3)

= 1/2 – 1/3

= (1 × 3 - 1 × 2)/(2 × 3)

= (3 - 2)/6

**
= 1/6
**

####
**
Add
**
**
(-1)/2
**
**
&
**
**
1/3
**

(-1)/2 + 1/3

= (-1 × 3 + 1 × 2)/(2 × 3)

= (-3 + 2)/6

**
= (-1)/6
**

####
**
Add
**
**
(-1)/2
**
**
&
**
**
(-1)/3
**

(-1)/2 + ((-1)/3)

= (-1)/2 – 1/3

= (-1 × 3 - 1 × 2)/(2 × 3)

= (-3 - 2)/6

= (-(3 + 2))/6

**
= (-5)/6
**